Effects of aspergillus niger and penicillium sp. on seed germination and seedling growth of rice (oryza sativa) and cron (zea mays) - Espiritu, Gerard Anthony M. 4 0 16; 5 (2005)
ABSTRACT: The study focused on the effects of Aspergillus niger and Penicillium sp. Inoculants on the Seed Germination and Seeding Growth of Rice (Oryza sativa) and Corn (Zea mays). Aspergillus niger and Penicillium sp. were used as treatments on Oryza sativa (Kinanda Puti Variety) and Zea mays (IES 906 - White Corn Variety). Three grams of both fungi were mixed with 500 grams of sun-dried, pulverized garden soil. Both the control and the treatments per plant had three blocks. Seed germination was determined by %germination per day. Seedling growth was determined by measuring the length of the shoot system in centimeters and length of the root system in centimeters after fifteen days. Using one-way ANOVA (Analysis of Variance), it was found that there was significant differences between the control and the treatments in terms of the seed germination of corn: Fc = 24 while Ft = 4.98. Two-sided comparisons between k treatment and a control (by C.W. Dunnett) was used to further determine which of the two treatments had an effect on the seed germination of corn. It was then found that only Penicillium sp. had an effect on the seed germination of corn in terms of its %germination: dtab = 2.90 and dpenicill = 6.41. However, both treatments had no effect in terms of the seed germination of rice and seedling growth of both test plants (rice and corn).
Thesis: (B.S. Biology)-Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2